THE CONTENT OF TEACHING SCIENCE OF EDUCATION IN PRIMARY CLASSES - Mahliyo Khaydarova (Scholar Express Journal, 2023)
This article talks about the scientific-theoretical foundations of education in primary classes, and at the same time, the attention paid to education and training in general education schools in our country, and the educational processes. The objective laws of education - the organization of the educational process and the development of individuality and qualities of people in social life, the further improvement of the first forms of education (educational knowledge received in the family) that students have, teachers, educators , it is based on the important task facing the coaches
Keywords: education; educational process; task; students